The benefits of nature experience: Improved affect and cognition - Bratman, Gregory N.; Daily, Gretchen C.; Levy, Benjamin J.; Gross, James J. (Landscape and urban planning, 2015)
•Nature experience produced clear benefits for affect (e.g., decrease in anxiety and rumination).•Nature experience produced some benefits for cognition (complex working memory span task).•Supports the idea that exposure to natural greenspace can improve affect and cognition. This study investigated the impact of nature experience on affect and cognition. We randomly assigned sixty participants to a 50-min walk in either a natural or an urban environment in and around Stanford, California. Before and after their walk, participants completed a series of psychological assessments of affective and cognitive functioning. Compared to the urban walk, the nature walk resulted in affective benefits (decreased anxiety, rumination, and negative affect, and preservation of positive affect) as well as cognitive benefits (increased working memory performance). This study extends previous research by demonstrating additional benefits of nature experience on affect and cognition through assessments of anxiety, rumination, and a complex measure of working memory (operation span task). These findings further our understanding of the influence of relatively brief nature experiences on affect and cognition, and help to lay the foundation for future research on the mechanisms underlying these effects.